2020
DOI: 10.1371/journal.pone.0230551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photobiomodulation on interleukin-10 and nitrites in individuals with relapsing-remitting multiple sclerosis – Randomized clinical trial

Abstract: Investigate the effects of photobiomodulation (PBM) on the expression of IL-10 and nitrites in individuals with Relapsing-Remitting multiple sclerosis (MS), as these biomarkers play a fundamental role in the physiopathology of the disease. The modulation of IL-10 and nitrites through treatment with PBM may be a novel treatment modality for MS. Methods A randomized, uncontrolled, clinical trial was conducted involving 14 individuals with a diagnosis of Relapsing-Remitting MS and a score of up to 6.0 on the Expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 14, 2021. ; https://doi.org/10.1101/2021.09.14.460393 doi: bioRxiv preprint 10 a range of neurological conditions, for example macular degeneration, Parkinson's disease, Alzheimer's disease, traumatic brain injury, stroke and multiple sclerosis (41 -48). There are also clinical reports of positive outcomes in aged humans and in patients suffering from many of these conditions (49)(50)(51)(52)(53)(54)(55)(56). Our findings, coupled with the highly conserved nature of the mechanism across species indicated that there are specific but limited times of day when this method is effective, but long periods when it is not; this feature could prove pivotal in achieving the maximum therapeutic outcome in both experimental laboratory and clinical settings.…”
Section: Discussionmentioning
confidence: 56%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 14, 2021. ; https://doi.org/10.1101/2021.09.14.460393 doi: bioRxiv preprint 10 a range of neurological conditions, for example macular degeneration, Parkinson's disease, Alzheimer's disease, traumatic brain injury, stroke and multiple sclerosis (41 -48). There are also clinical reports of positive outcomes in aged humans and in patients suffering from many of these conditions (49)(50)(51)(52)(53)(54)(55)(56). Our findings, coupled with the highly conserved nature of the mechanism across species indicated that there are specific but limited times of day when this method is effective, but long periods when it is not; this feature could prove pivotal in achieving the maximum therapeutic outcome in both experimental laboratory and clinical settings.…”
Section: Discussionmentioning
confidence: 56%
“…The changes in IL-10 values have been studied by other authors. Silva et al note that the reference values for IL-10 in individuals with MS are scarce [ 22 ]. According to Kwilasz et al, the IL-10 levels in peripheral-blood mononuclear cells are lower in individuals with MS compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…61 Interestingly, another randomized clinical trial on 14 MS patients showed that photobiomodulation (wavelength: 808 nm; power output: 100 mW) successfully induced the expression of the serum IL-10 anti-inflammatory cytokine in the MS patient with no statistical difference in nitrites levels. 62 It was also reported that LLLT had a great impact on optic nerve improvement in MS individuals. 63 Mesenchymal stem cells (MSCs) are multipotent stem cells and have great immunomodulatory properties and differentiation abilities.…”
Section: Effect Of the Laser On The Central Nervous Systemmentioning
confidence: 97%